Development of a practical and scalable route for the preparation of the deacetoxytubuvaline (dTuv) fragment of pretubulysin and analogs. Issue 8 (24th February 2016) - Brindisi, Margherita; Maramai, Samuele; Grillo, Alessandro; Brogi, Simone; Butini, Stefania; Novellino, Ettore; Campiani, Giuseppe; Gemma, Sandra
Graphical abstract: Highlights: Set-up of a novel route for the scaling-up of the dTuv fragment of pretubulysin. The optimized route starts from the inexpensive and non-toxic l -cysteine. The novel approach displays a dramatically increased overall yield. The newly conceived path allowed the preparation of three novel fragments. Abstract: We present herein a novel and convenient route for the scaling-up of the dTuv fragment of pretubulysin. The newly conceived chemical path involves a practical and efficient one-step procedure for the preparation of a key thiazole intermediate, followed by high-yielding Wittig olefination/reduction steps. The optimized route, starting from the inexpensive and non-toxic l -cysteine, encompasses five synthetic steps and only two chromatographic purifications, thus displaying a dramatically increased overall yield. The versatility of the proposed approach also provides new hints for the exploration of pretubulysin derivatives bearing diverse heterocyclic portions.